Fame & fortune : how successful companies build winning reputations - Fombrun, Charles J. (Financial Times Prentice Hall books., 2004)
Companies build reputations in the market place. Some do it well, others don't. Even well-managed, profitable, quality companies don't. The how and why of successful reputation building is what this book is about. What specific actions must companies take to build a positive reputation in the market place? How can a company measure the success of its attempts to build a positive reputation in the market place as well.